Metagenomics of Thermophiles with a Focus on Discovery of Novel Thermozymes - DeCastro, María-Eugenia; Rodríguez-Belmonte, Esther; González-Siso, María-Isabel (Frontiers in Microbiology, 2016)
Microbial populations living in environments with temperatures above 50ºC (thermophiles) have been widely studied, increasing our knowledge in the composition and function of these ecological communities. Since these populations express a broad number of heat-resistant enzymes (thermozymes), they also represent an important source for novel biocatalysts that can be potentially used in industrial processes. The integrated study of the whole-community DNA from an environment, known as metagenomics, coupled with the development of next generation sequencing (NGS) technologies, has allowed the generation of large amounts of data from thermophiles. In this review, we summarize the main approaches commonly utilized for assessing the taxonomic and functional diversity of thermophiles through metagenomics, including several bioinformatics tools and some metagenome-derived methods to isolate their thermozymes.